Sero-incidence of brucellosis in small ruminants of semiarid Rajasthan - SONAWANE, G G; TRIPATHI, SUSHIL; DUBEY, S C (The Indian Journal of Animal Sciences, 2011)
The present study was taken up to ascertain the prevalence of brucellosis in sheep and goats of semiarid region of Rajasthan by Rose Bengal Plate Test and commercially available ELISA kit. RBPT detected brucella antibodies in 94 (8.82%) out of 1065 and ELISA in 118 (11.47%) out of 472 sheep serum samples tested. The highest seroprevalence was recorded in Tonk (24.47% and 43.29%), followed by Ajmer district (11.16% and 14.06%) by RBPT and ELISA, respectively. RBPT detected Brucella antibodies in 12 (1.65%) out of 723 and ELISA detected 19 (4.67%) out of 406 goat serum samples. The incidence in Tonk district was 1.31% and 10.44%, in Ajmer 2.20% and 2.63%, in Bundi 1.75% and 1.85%, and in Bhilwara 3.4% and 5.47%, by RBPT and ELISA, respectively. The combined incidence in sheep and goats of semiarid Rajasthan was 5.92% by RBPT and 15.6% by ELISA. Our results showed higher seroprevalences in small ruminants of Tonk, Bhilwara and Ajmer districts. There is a need to screen human population dealing with husbandry, health and marketing of small ruminants and to develop effective control and prevention strategies for sheep and goats of this area against brucellosis.